Health information technology: Anticipating, recognizing, and preventing disruptions in complex adaptive healthcare systems - Palmieri, Patrick Albert (2014)
Healthcare organizations are increasingly willing to develop more efficient and higher quality processes to combat the competition and enhance financial viability by adopting contemporary solutions such as Health Information Technology (HIT). However, technological failures occur and represent a contemporary organizational development priority resulting from incongruent organization-technology interfaces. Technologically induced system failure has been defined as technological iatrogenesis. The chapter offers the Healthcare Iatrogenesis Model as an organizational development strategy to guide the responsible implementation of HIT projects. By recognizing the etiology of incongruent organizational interfaces and anticipating patient safety concerns, leaders can proactively respond to system limitations and identify hidden process instabilities prior to costly and consequential catastrophic events. © 2015 by IGI Global. All rights reserved.